Droplet coalescence: drainage, film rupture and neck growth in ultralow interfacial tension systems - Aarts, D; Lekkerkerker, H (2008)
We study the coalescence of a drop with its bulk phase in fluid-fluid demixing colloid-polymer mixtures. Such mixtures show behaviour analogous to molecular fluid-fluid systems, but the interfacial tension is between 105 to 107 times smaller than in the molecular case. Such an ultralow interfacial tension has several important consequences and offers significant advantages in the study of droplet coalescence. The coalescence process can be divided into three consecutive stages: (i) drainage of the continuous film between droplet and bulk phase, (ii) rupture of the film, and (iii) growth of the connection. These stages can be studied within a single experiment by optical microscopy thanks to the ultralow interfacial tension in colloid-polymer mixtures, which significantly changes the relevant characteristic length and time scales. The first stage is compared with existing theories on drainage, where we show several limiting theoretical cases. The experimental drainage curves of different colloid-polymer mixtures can be scaled and then show very similar behaviour. We observe that drainage becomes very slow and eventually the breakup of the film is induced by thermal capillary waves. The time it takes for a certain height fluctuation of the interface to occur, which turns out to be an important parameter for the kinetics of the process, can be directly obtained from experiment. During the third stage we observe that the radius of the connecting neck grows linearly with time both for gas bubbles and liquid droplets with an order of magnitude that is in good agreement with the capillary velocity. Finally, partially bleaching the fluorescent dye inside the liquid droplet reveals how the surface energy is transformed into kinetic energy upon coalescence. This opens the way for a more complete understanding of the hydrodynamics involved. © 2008 Cambridge University Press.